MIKROALGA LAUT Nannochloropsis Oculata SEBAGAI ALTERNATIF ANTIVIRUS Viral Nervous Necrotic (VNN) PADAIKAN KERAPU TIKUS (Cromileptes Altivelis) - Ach. Khumaidi (Samakia : Jurnal Ilmu Perikanan, 2016)
Viral nervous necrosis (VNN) is the causative agent of the disease that quite dangerous for the survival of grouper farming (C. altivelis). Impacts this virus attacks are capable of causing up to 100% mortality. For overcome attack VNN can be used materials of biological resources is N. oculata. Utilization marine microalgae N. oculata were able to improve the immune system, boost the immune response by improving the expression of Toll-like Receptor (TLR) expression Major Histocompitability Complex (MHC), were able to inducing antiviral genes (P56), and able to provide an anti-inflammatory effect. With these capabilities. Feasible to develop the utilization of marine microalgae N. oculata as an alternative to tackling VNN attack on C. altivelis.